Pengertian Radikalisme dalam Konteks Politik dan Implikasinya dalam Persatuan NKRI - St. Haniah; Abd. Basir; M. Daud Yahya; Gia Ayu Fita; Aloysius Jondar (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
This paper focuses on the emergence of nuanced political radicalism in various official forums and social media, which are believed to have implications for the integrity of the Unitary Republic of Indonesia. This research is qualitative with a literature review. The literature review is under discussion by looking for references related to issues and acts of radicalism that threaten national unity. The data analysis collects various references related to the discussion carried out and examines them from several references. This research finds that the issues and actions that occur in Indonesia are not new because of the existence of groups that are not in line with the government's thinking so that in political nuances, this becomes a very urgent matter. The state considers this problem to have implications for the existence of the current ruler. At the same time, radicalism has been increasingly heard since the digital era, where all citizens, who practice and sympathize with others, will all be channeled through the internet so that issues of radicalism and the power of unity can be found through internet access.